Digitalisasi Administrasi untuk Efektivitas Penanganan Perkara Perdata di Law Office Denpasar Barat - Lani Theana Wirawan; Ni Luh Putu Sariani (JURPIKAT (Jurnal Pengabdian Kepada Masyarakat), 2025)
This community service activity was carried out at the Law Office of I Made Ardana SH., MH., CIL., CPL., CPCLE., CBLC & Partners, located at Jalan Teuku Umar No. 121, Investama Block V, West Denpasar. The background of the activity is the continued use of manual recording, which risks causing delays in access to information and data errors. The main objective is to improve efficiency and accuracy through a digital system. The implementation was carried out in three stages: observation and discussion of needs, assistance in using Microsoft Excel, and evaluation through questionnaires. The results show that digitization facilitates record-keeping, speeds up access to information, and promotes a technology-based work culture. However, further training is still needed so that staff can adapt more optimally.